Nanopatterned Silicon Substrate Use in Heterojunction Thin Film Solar Cells Made by Magnetron Sputtering - Shao-Ze Tseng; Chang-Rong Lin; Hung-Sen Wei; Chia-Hua Chan; Sheng-Hui Chen (International Journal of Photoenergy)
This paper describes a method for fabricating silicon heterojunction thin film solar cells with an ITO/p-type a-Si : H/n-type c-Si structure by radiofrequency magnetron sputtering. A short-circuit current density and efficiency of 28.80 mA/cm2 and 8.67% were achieved. Novel nanopatterned silicon wafers for use in cells are presented. Improved heterojunction cells are formed on a nanopatterned silicon substrate that is prepared with a self-assembled monolayer of SiO2 nanospheres with a diameter of 550 nm used as an etching mask. The efficiency of the nanopattern silicon substrate heterojunction cells was 31.49% greater than that of heterojunction cells on a flat silicon wafer.